The sodium channel β1 subunit mediates outgrowth of neurite‐like processes on breast cancer cells and promotes tumour growth and metastasis. Issue 10 (26th April 2014) - Nelson, Michaela; Millican‐Slater, Rebecca; Forrest, Lorna C.; Brackenbury, William J.
<x xml:space="preserve">Abstract</x> Voltage‐gated Na+ channels (VGSCs) are heteromeric proteins composed of pore‐forming α subunits and smaller β subunits. The β subunits are multifunctional channel modulators and are members of the immunoglobulin superfamily of cell adhesion molecules (CAMs). β1, encoded by SCN1B, is best characterized in the central nervous system (CNS), where it plays a critical role in regulating electrical excitability, neurite outgrowth and migration during development. β1 is also expressed in breast cancer (BCa) cell lines, where it regulates adhesion and migration in vitro. In the present study, we found that SCN1B mRNA/β1 protein were up‐regulated in BCa specimens, compared with normal breast tissue. β1 upregulation substantially increased tumour growth and metastasis in a xenograft model of BCa. β1 over‐expression also increased vascularization and reduced apoptosis in the primary tumours, and β1 over‐expressing tumour cells had an elongate morphology. In vitro, β1 potentiated outgrowth of processes from BCa cells co‐cultured with fibroblasts, via trans‐homophilic adhesion. β1‐mediated process outgrowth in BCa cells required the presence and activity of fyn kinase, and Na+ current, thus replicating the mechanism by which β1 regulates neurite outgrowth in CNS neurons. We conclude that when present in breast tumours, β1 enhances pathological growth and cellular dissemination. This study is the first demonstration of a functional role for β1 in tumour growth and metastasis in vivo. We propose that β1 warrants further study as a potential biomarker and targeting β1‐mediated adhesion interactions may have value as a novel anti‐cancer therapy.